TouchLib© 2.0 - Amno, Hasniza; Shaharuddin, Bakiah; Kasim, Mohd Jamil; Salis @ Saleh, Md Naim; Hashim, Siti Fatimah (Universiti Teknologi MARA, Kedah, 2019)
TouchLib was an innovative system which was developed using a VB6 programming language and PHP to track records and monitors the library users at Advanced Medical and Dental Institute (AMDI), Universiti Sains Malaysia, Kepala Batas, Pulau Pinang. AMDI is an advanced academic institute recognized for post graduate programmes, high impact research studies and tertiary level clinical services. TouchLib was a unique in-house system; which was designed to be flexible to fit the organisation’s purposes, and require no extra investment. This system is advantageous due to its simplicity and cost-effectiveness. A library user is tracked with the tapping (touching) of their identification card (staff or student card) to the Library Automation System that is KOHA. It records the date and time that users are admitted in and out of the library. Here the system combines data from the university’s human resource system (HCMS) and the student’s database (SMU) to record staff and students’ attendance/admission. The system provides a convenient way to recognise registered users, including their photo and profiles from non-registered users; as a requirement before using the library facilities and services. The system is also able to record the loan service activity of any library materials as databased in KOHA. TouchLib system uses an open source database known as “MySQL” which has unlimited record and data storage. Since its inception in May 2018, the system has empowered AMDI library to escalate its programmes and assisted in future plans and upgrading of our services. The latter is made possible by an automated link to a feedback form sent to all tracked users by this system. TouchLib copyright registration number is LY201 8005 416.